Reflective Portfolios as decolonial pedagogical practices - Crespo Lopes, Juliana; Stará, Jana (Educar em Revista, 2022)
Pre-service teachers learn educational practices and teaching postures not only from the courses content but also by their teachers’ approaches. Learning assessments can be used as an exercise of power that perpetuates an established colonial paradigm. Conversely, Reflective Portfolios can be conceived as an opportunity for new arising knowledge and practices. In this paper we connect teaching experiences using Reflective Portfolios with scientific literature inserting them into the context of the decolonial studies. When pre-service teachers perceive themselves as epistemological beings, they understand that knowledge derives from different sources. Consequently, they have new possibilities of pedagogical postures and practices in their future profession. Furthermore, reflective portfolio assessments grant the opportunity for university teachers to rethink practices and postures that might endorse educational power structures, to find out more about their students, and to provide formative opportunities